La muerte digna como componente de un derecho a vivir en dignidad. Argumentos a favor de la despenalización de la eutanasia - Caro John, José Antonio (Derecho penal y criminología, 2023)
The current investigation presents ideas in favor of the non-criminality of the euthanasia act based on an understanding of the value of life for Criminal Law, as an exercise of dignity and not as the enjoyment of a psychobiological function. Denying euthanasia to whom suffers from an irreversible and degenerative disease is also forcing them to endure a state of mechanical continuity as a way of life, depriving them of their autonomy and decision to end to the state of indignity or reification caused by the disease. However, in order to the avoid the confusion of seeing the euthanasia as just an act of killing an incurable patient, and to not assume that it is practiced without a rational reason, the euthanasia act must be carried out in accordance with the protocols of the lex artis in the medical field and in observance of the professional scientific standard. Therefore, the doctor who performs euthanasia, will be contributing to optimizing the autonomy of the patient who wishes to end its existence due the suffering and progressive reification and will carry out an act within the limits of the permitted risk, and it will not be objectively imputable to him. In this way, euthanasia will truly be the result of a cessation of life procedure as an act of defense of the value of living with dignity.